Satisfying the multiple needs of older adults in rural China through the adaptation of dual polycentric systems - Xiaowei Dong; Siwen Qian (Humanities & Social Sciences Communications, 2024)
Abstract This study explores the fulfillment of multiple needs of older adults in rural China by adapting and aligning two polycentric systems from the perspective of intergenerational relationships. Utilizing the fuzzy-set Qualitative Comparative Analysis (fsQCA) methodology, it pinpoints crucial nesting points that facilitate the integration of the two systems. The study emphasizes maximizing the potential of these nesting points to achieve a cohesive systemic structure. Consequently, it suggests the development of an organizational-level polycentric framework that integrates the comparative advantages (on exploiting various nesting points) of various entities such as nuclear families, village self-governing organizations, government agencies, commercial enterprises, educational institutions, and others. This framework is capable of leveraging its spontaneous order to effectively tackle the challenges associated with ageing in rural areas. This study addresses the gap in the literature concerning an in-depth understanding of tackling rural ageing issues using a polycentric lens.